Eremomastax speciosa potentializes the PMSG-inducing effect on some physiological and biochemical parameters in PMSG-primed immature rats. Issue 6 (12th December 2020) - Mbemya, Gildas Tetaping; Chekem, Marie Stéphanie Goka; Lienou, Landry Lienou; Sylvain, Njina Nguedia; Donfack, Jiatsa Nathalie; Guerreiro, Denise Damasceno; Njimou, Jacques Romain; Rodrigues, Ana Paula Ribeiro; Telefo, Phélix Bruno
Summary: The present study evaluated the effect of the aqueous extract from leaves of E . speciosa on some physiological and biochemical parameters of reproduction and the onset of puberty in pregnant mare serum gonadotropin (PMSG)-primed immature female rats. High pressure liquid chromatography (HPLC) was used to quantify the phenolic compounds in the methanol/methylene chloride (1:1) extract, the ethanolic and ethyl acetate fractions and the aqueous residue of E . speciosa . E . speciosa (0, 8, 32 or 64 mg/kg) were administered for 15 days to 24 non-PMSG-primed and 24 primed rats with 0.01 IU of PMSG. At the end of the treatment period, animal were sacrificed and their body, ovarian, uterine weight, ovarian protein or cholesterol level, as well as data on puberty onset were recorded. Of the 16 polyphenolic compounds quantitatively revealed in the extracts and fractions of E . speciosa after HPLC analysis, quercetin, rutin, apigenin and eugenol were the most abundant. Non-primed rats showed a significant increase ( P < 0.05) in the uterine relative weight at the dose of 8 mg/kg when compared with the other treatments. The uterine proteins and the ovarian cholesterol ( P < 0.05), respectively, showed a reduction at doses of 64 mg/kg and 32 mg/kg in non-primed rats. However in PMSG-primed rats, a significant decrease ( P < 0.05) was observed in ovarian cholesterol at 64 mg/kg. In conclusion, E . speciosa potentializes the PMSG-inducing effect on folliculogenesis in PMSG-primed rats.